THE EFFECT OF THE BRAIN-BASED LEARNING (BBL) MODEL ON THE LEARNING OUTCOMES OF 5TH GRADE STUDENTS OF SD NEGERI 105288 SEI ROTAN - Silalahi, Alda Alviola; Manurung, Imelda Free Unita (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research is motivated by the existence of problems in learning, especially in class V of SD Negeri 105288 Sei Rotan. Through the results of observations and interviews, it was found that the results of students' science learning are classified as low. In addition, student participation is low and passive. The purpose of this study is to determine the effect of the application of the Brain Based Learning (BBL) learning model on the results of science learning of class V students of SD Neri 105288 Sei Rotan. The type of research used is quantitative research with a nonequivalent control group design. The population in this study were class V students of SD Negeri 105288 Sei Rotan with a sample of class VA totaling 24 people as the experimental class and VB totaling 24 people as the control class. Based on the results of the study, the average pretest score of students was 52.33 in the experimental class before being given treatment. After treatment using the BBL learning model, the results of the posttest score of students were 71.25. Furthermore, a t-test was conducted which showed the results of the Sig. value. (2 tailed) 0.000 < 0.05, then H0 is rejected and Ha is accepted. These results indicate that there is a significant influence of the application of the Brain Based Learning (BBL) learning model on the science learning outcomes of fifth grade students of SD Negeri 105288 Sei Rotan.